The role of mothers in the first 1000 days of life in preventing child developmental disorders - Marina, Marina (CV. Paperhome Indonesia, 2024)
The first thousand days of life (1000 HPK) is a child's golden period to grow and develop optimally. Disturbances that occur in This period has an impact on the child's survival and growth and development are permanent and long-term and more difficult to repair after the child is 2 years old. The aim of this service is to improve knowledge of the importance of the role of mothers during the 1000 HPK period in prevention the occurrence of growth and development disorders in children. The method used is counseling, discussions and questions and answers to 20 mothers who have children aged 0-24 months. The results show that before counseling was carried out, some Most mothers don't know about 1000HPK and the impacts it has on child growth and development. However, after counseling, Participants' knowledge and understanding of 1000 HPK increased by around 94.8%. Advice for parents to regularly bring and check their children every month to health services and providing adequate nutritional intake to support optimal growth and development